Devotion at Sub-National Level: Ramadan, Nighttime Lights, and Religiosity in the Egyptian Governorates. (3rd December 2020) - Ciftci, Sabri; Robbins, Michael; Zaytseva, Sofya
Abstract: This study aims to construct reliable measures of religiosity and to cross-validate survey-based measures in operationalization of this central variable. We obtain measures of sub-national religiosity in the Egyptian governorates from the Arab Barometer surveys using disaggregation and multilevel regression and post-stratification techniques. Then, we use satellite imagery to compare these measures to the intensity of nighttime lights during the holy month of Ramadan. Although not designed to be fully representative, the analysis reveals that survey data at the sub-national level can provide approximate measures when aggregated. These findings contribute to scholarship by introducing a novel measure of religiosity based on nighttime activity during Ramadan and by cross-validating the reliability of survey-based measures of aggregate religiosity.